Pengembangan Tata Kelola Madrasah Berbasis Pesantren - Usup Supriatna (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2023)
This research is to find out about the development of private madrasah management in private MA Miftahul Falah. The results of this study indicate that the development of management is in accordance with planning, organizing, implementing, and evaluating, except for the aspects of financing that have not been optimal. As for the Gedebage and private MA YPP Sukamiskin, it can be concluded that the development of madrasah management is in accordance with the plan, except in the aspect of financing, which only relies on BOS and causes delays in all activities.